Long-term CCNC measurements at the central European ACTRIS research station Melpitz, Germany, 2012-2016 - Wang, Yuan; Henning, Silvia; Poulain, Laurent; Stratmann, Frank; Herrmann, Hartmut; Wiedensohler, Alfred (In: Wang, Y et al. (2021): Long-term CCN measurements at the central European ACTRIS research station Melpitz, Germany [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.938215, 2021)
Atmospheric aerosol measurements were conducted at the Melpitz observatory, Germany. The data was collected during 2012 to 2016, measured by Droplet Measurement Technologies Cloud Condensation Nucleus Counter (DMT-CCNC).
Keywords: Aerosol chemistry; Cloud Concensation Nuclei; Particle Number Size Distribution (PNSD)